1999
DOI: 10.1159/000016550
|View full text |Cite
|
Sign up to set email alerts
|

Powdered Milk Micellar Casein Prevents Oral Colonization by <i>Streptococcus sobrinus</i> and Dental Caries in Rats: A Basis for the Caries–Protective Effect of Dairy Products

Abstract: Three animal studies were performed to investigate the influence of the macromolecular structure of milk casein on caries incidence and the possible ecological changes of the oral microbiota by such casein fractions. Towards this end, rats were infected with mixed bacterial suspensions of Streptococcus sobrinus OMZ 176 and Actinomyces viscosus Ny1. Various milk protein fractions were incorporated into carefully balanced powdered cariogenic diets to constitute the sole major protein component. Diets containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 31 publications
1
41
0
3
Order By: Relevance
“…The peptide released by natural digestion of casein in the stomach, with chymosin, CMP (11) has been shown to substantially inhibit the adherence of Streptococcus mutans to salivary pellicle (17,21,25,26), and this has been proposed to be the mechanism of anticariogenicity of milk protein fractions in animal caries models (7). In this study we have shown that CMP has growth-inhibitory activity against S. mutans and P. gingivalis as well as E. coli.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…The peptide released by natural digestion of casein in the stomach, with chymosin, CMP (11) has been shown to substantially inhibit the adherence of Streptococcus mutans to salivary pellicle (17,21,25,26), and this has been proposed to be the mechanism of anticariogenicity of milk protein fractions in animal caries models (7). In this study we have shown that CMP has growth-inhibitory activity against S. mutans and P. gingivalis as well as E. coli.…”
Section: Discussionmentioning
confidence: 73%
“…CMP has also been shown to incorporate into salivary pellicle and inhibit the adherence of Streptococcus mutans, the oral pathogen implicated in the development of dental caries (12,17,21,25,26). The incorporation of CMP into salivary pellicle is proposed to be the mechanism by which certain milk protein fractions, when added to the cariogenic diet of rats, substantially reduce caries activity and the recovery of mutans group streptococci from the experimental animals (7). Examination of the amino acid sequence of CMP revealed that the peptide contains residues that could form an amphipathic helical structure, and as such, the peptide may possess antibacterial properties.…”
mentioning
confidence: 99%
“…Casein also plays an important role. Micellar casein selectively modifies the microbial composition of dental plaque [28]. Casein phosphopeptides react with high concentrations of calcium and phosphate to form calcium phosphate complexes.…”
Section: Protective Effect For Dental Cariesmentioning
confidence: 99%
“…While most of these agents, such as chlorhexidine or essential oils, aim at killing bacteria in the oral cavity, non-bactericidal approaches that target bacterial adhesion and biofilm formation have gained increasing attention in recent years [8][9]. In particular, milk proteins, such as lactoferrin, alactalbumin and caseins have been shown to interfere with the adhesion and biofilm formation of oral organisms [10][11][12][13][14]. Since the development of a robust biofilm is a prerequisite for the establishment of highly acidic microenvironments at the tooth surface, these therapeutic approaches possess great potential for caries prevention.…”
Section: Introductionmentioning
confidence: 99%